Yang Terbuang, Yang Membangun: Studi Perubahan Sosial Di Kecamatan Waeapo Kabupaten Buru Oleh Eks Orang-Orang Buangan 1969-1979 - Naomi Lesbatta; Widhi Handayani; Pamerdi Giri Wiloso (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
Buru Regency is one of the rice suppliers in Maluku Province.The achievements of Buru Regency as Maluku rice supplier cannot be separated from its history as a place for people who were exiled in 1969. The presence of these former people has an influence on social change in Buru Island. Located in Waeapo district, Buru regency, this qualitative research was conducted to explain social change in Waeapo, Buru by the former exiles. The results showed that before the former exiles arrived at Buru Island, the Waeapo was dominated by forests, where the local people practiced swidden agriculture. The presence of former exiles in 1969 changed the landscape of Buru from forest to paddyfields by means of forced labor. The forced labor and introduction of new agricultural system are patterns inherited from the colonial government. Nevertheless, in Buru, the harvest was consumed by the exiles instead of handed over to the government as a custom enforced by the colonials. The change in land use eventually changed the shifting cultivation system to permanent agriculture with the lowland rice farming system which is commonly practiced in Java. Ex-exiles were the people used by the New Order government to carry out development in remote areas in the 1969-1979 era until the change of Buru’s landscape, source of staple food, and cultural diversity exist in Waeapo..